1982
DOI: 10.1021/bi00257a038
|View full text |Cite
|
Sign up to set email alerts
|

Human skeletal growth factor: characterization of the mitogenic effect on bone cells in vitro

Abstract: preincubated with the factor for 5-6 h were incubated in factor-free medium), suggesting that the effect is inductive. Actual counts of calvarial cells in culture revealed that in response to added factor, both cell number and maximum cell density (161% of controls, p < 0.001) were increased. This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A substance referred to as human skeletal growth factor has been isolated from human bone and shown to increase DNA synthesis in bone cells, stimulate osteoblast proliferation, and induce bone formation [ 65 ]. Similar and possibly identical factors are present in bone from other species [63].…”
Section: Reversalmentioning
confidence: 99%
“…A substance referred to as human skeletal growth factor has been isolated from human bone and shown to increase DNA synthesis in bone cells, stimulate osteoblast proliferation, and induce bone formation [ 65 ]. Similar and possibly identical factors are present in bone from other species [63].…”
Section: Reversalmentioning
confidence: 99%
“…In addition, skeletal growth factor and transforming growth factor-,3-like activity were found in extracts of bovine bone matrix (25) and skeletal growth factor was present in abstracts of human bone (24). The component(s) responsible for the mitogenic activity in DABM in the present studies has not been identified.…”
Section: Discussionmentioning
confidence: 59%
“…Skeletal growth factor is a high molecular weight protein isolated from adult bones of human and several other species such as bovine, porcine, rat, and chick [10][11][12]. Human skeletal growth factor, purified by nondenaturing polyacrylamide gel electrophoresis, was found to have an apparent molecular weight of 83,000 daltons.…”
Section: Properties Of Hsgf: Chemical and Biologicalmentioning
confidence: 99%
“…Its activity is sensitive to trypsin and resistant to inactivation by heat, extremes of pH, collagenase, and reducing agents [10]. It stimulated DNA synthesis several hours after its addition to quiescent cells [ 11 ]. Human skeletal growth factor has been found to stimulate 3H-thymidine incorporation in mesodermal cells: cultured chick embryo bone cells and cartilage cells, human bone cells and skin cells, osteosarcoma cells, chick embryo skin cells, and Balb/C 3T3 cells [12].…”
Section: Properties Of Hsgf: Chemical and Biologicalmentioning
confidence: 99%
See 1 more Smart Citation